PENERAPAN MODEL PEMBELAJARAN INKUIRI BERBASIS LABORATORIUM UNTUK MEREMEDIASI MISKONSEPSI PESERTA DIDIK TENTANG GETARAN - Asmadi Asmadi; Edy Tandililing; Syukran Mursyid (Universitas Tanjungpura, 2019)
AbstractThis study aims to determine the effectiveness of the inquiry based laboratory learning models implementation to reduce the percentage of VIII grade students’ misconceptions about vibrations in SMP Negeri 3 Pontianak. The form of this research is pre-experimental design with one group pretest-posttest design. There were 35 students in VIII I assigned as samples using the intact group technique. Data collection uses diagnostic tests through pre-test and post-test. It was found that the average percentage of students who misconceptions in the pre-test was 48.3% and in the post-test amounted to 8.67%. The decrease of students who misconception on average is 83%. The results of calculations using the McNemar test obtained χ2count is 12.07 greater than χ2table that is 3.841. Students’ conceptual changed significantly after the remediation activity using inquiry based laboratory learning model about vibration. The remediation effectiveness based on DQM test in average is 82.54% (high category). The inquiry based laboratory learning model is expected to be an alternative learning to overcome students' misconceptions about vibration. Keywords: Inquiry Based Laboratory Learning Model, Misconception, Remediation, Vibration